Antioxidant: Antimycobacterial and Antibiofilm Activities of Acetone Extract and Subfraction Artemisia afra Jacq. ex Willd. Against Mycobacterium smegmatis - Mabasa Precious Matlala; Mashilo Mash Matotoka; Wanda Shekwa; Peter Masoko (Antibiotics)
Tuberculosis is a worldwide prevalent and recurring disease that contributes significantly to high mortality rates. This study aimed to investigate the antioxidant, anti-mycobacterial, and antibiofilm activities of Artemisia afra acetone crude extract. Methodology: The crude acetone extract was fractionated using column chromatography and characterized by liquid chromatography–mass spectroscopy (LC-MS). A 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging assay was used to assess the antioxidant activity. The antimycobacterial activity against Mycobacterium smegmatis was screened using bioautography, broth microdilution, and growth curve assays. Molecular docking was used to predict the possible mechanisms of action of the LC-MS-identified ligands. Crystal violet was used to screen for anti-cell adherence and biofilm inhibition activities. Results: The crude extract scavenged 77% of the free radical at 16 μg/mL. The subfraction had a lower minimum inhibitory concentration (MIC) (0.078 mg/mL) compared to the crude extract (0.313–0.833 mg/mL). The subfraction had a concentration-dependent inhibition effect (>50%) on mycobacterial cell adherence and early biofilms. However, the mature biofilms were resistant. Two propanoate compounds, [(2S)-3-[6-acetyl-4,6-dihydroxy-3-[(1R)-1-hydroxyethyl]tetrahydropyran-2-yl]-2-hydroxy-propyl] (2R)-2-amino-3-(1H-imidazol-5-yl)propanoate and 3-(6-aminopurin-9-yl)propyl 3-(2,4-dioxo-1,3-diazaspiro[4.5]decan-3-yl) propanoate, had binding energies of −5.4 kcal/mol and −6.3 kcal/mol, respectively, against the RNA polymerase binding protein. Conclusions: The results show that A. afra acetone crude extract has antioxidant and antimycobacterial activities that can be improved by fractionation.